2020
DOI: 10.1103/physrevd.101.083031
|View full text |Cite
|
Sign up to set email alerts
|

Repeated gravitational lensing of gravitational waves in hierarchical black hole triples

Abstract: We consider binary black holes (BBHs) in a hierarchical triple system where a more compact, less-massive binary is emitting detectable gravitational waves (GWs), and the tertiary is a supermassive BH at the center of a nuclear star cluster. As previous works have shown, the orbital motion of the outer binary can generate a detectable relativistic Doppler boost of the GWs emitted by the orbiting inner binary. We show here that for outer-binary orbits with a period of order one year, there can be a non-negligibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 71 publications
0
41
0
Order By: Relevance
“…Approximating the lens as a point mass (as we typically have a o ∼ 100-1000M 3 ≫ M 3 for systems of interest), we then have a time-dependent Fðt; fÞ as [57] (see also Refs. [46,61]; note that this is applied only when x o > 0 or the source is behind the lens) ηðtÞ is defined as ηðtÞ ¼ βðtÞ=θ Ein ðtÞ, where θ Ein ðtÞ ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi 4M 3 D LS ðtÞ=ðD OS D OL Þ p is the angular Einstein radius. Under the SPA, the time t can be further treated as a function of f via Eq.…”
Section: A Standard Lensing In the Weak-deflection Limitmentioning
confidence: 99%
See 4 more Smart Citations
“…Approximating the lens as a point mass (as we typically have a o ∼ 100-1000M 3 ≫ M 3 for systems of interest), we then have a time-dependent Fðt; fÞ as [57] (see also Refs. [46,61]; note that this is applied only when x o > 0 or the source is behind the lens) ηðtÞ is defined as ηðtÞ ¼ βðtÞ=θ Ein ðtÞ, where θ Ein ðtÞ ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi 4M 3 D LS ðtÞ=ðD OS D OL Þ p is the angular Einstein radius. Under the SPA, the time t can be further treated as a function of f via Eq.…”
Section: A Standard Lensing In the Weak-deflection Limitmentioning
confidence: 99%
“…Recently, Ref. [46] further considered the strong gravitational lensing of the BBH's GW caused by the SMBH and showed that there is a high geometrical probability (∼10%) for lensing to happen if the BBH is in an outer orbit with a period of less than a year (shorter than the duration of the observation). Reference [46] referred to this as "repeated lensing."…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations